Assessing nutrient leaching in red-yellow latosol: The role of swine water and irrigation water reuse - Talita Dantas Pedrosa, Henrique Takyiuki Ozima, Roselene Maria Schneider , Adilson Pacheco de Souza, Ednaldo Antonio de Andrade, Luciana Vieira Mattos (African Journal of Pig Farming, 2023)
This study evaluates some micro- elements, phosphorus, copper and zinc leached in lysimeters with red-yellow Latosol under different rates of reused water and irrigation water. This was done for a period of 40 days (August to October 2014) at the initial cycle of cauliflower cultivar ‘Verona CMS’, in Sinop/Mato Grosso. Reused swine water (0, 50 and 150 m3 ha-1 ) was applied in one portion before transplanting. Irrigation water of 100, 125 and 150% with crop evapotranspiration potential (ETc) was used in a drip irrigation system daily. Leachate samples were taken at 10, 20, 30 and 40 days after applying the reused water. With balanced leached phosphorus (P), a higher percentage of P retained in the soil was observed, indicating low mobility of this element. The concentrations of copper in the leachate were low at 150 m3 ha-1 rate after the reuse of swine water, at day 20. 150 m3 ha-1 used in the irrigated lysimeters with 100% ETc is a good alternative for vegetable crops with a short cycle (less than 40 days), in Sinop/Mato Grosso, as it does not exceed the limits of the Conama Resolution No. 396/2008